2017
DOI: 10.3846/13923730.2016.1210221
|View full text |Cite
|
Sign up to set email alerts
|

Applications of stiffness-based evaluation method to element importance of truss systems

Abstract: Two structural performance indexes, making use of eigenvalues of stiffness matrix, are presented in the study for the evaluation of element importance in the progressive collapse analysis of space trusses. Both indexes are based on the consensus that the element transferring higher loads in the load path is generally more important in the structural sys­tem. The first index is formulated as change of the smallest stiffness after removal of specific element, and the second in­dex is defined as determinant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Miyachi, Nakamura, and Manda (2012) used the ultimate strength as a comparative parameter to assess robustness for different bridge truss design alternatives. More recently, Cai, Jia, Feng, Wang, and Xu (2017) proposed two performance indicators, the first one making use of the eigenvalues of stiffness matrix and the second based on the tangent stiffness of the structure. In addition, the stiffness-based vulnerability theory was seen to be used to identify the collapse mechanism or failure scenarios Ye, Liu, & Pan, 2011).…”
Section: Deterministic Indicesmentioning
confidence: 99%
“…Miyachi, Nakamura, and Manda (2012) used the ultimate strength as a comparative parameter to assess robustness for different bridge truss design alternatives. More recently, Cai, Jia, Feng, Wang, and Xu (2017) proposed two performance indicators, the first one making use of the eigenvalues of stiffness matrix and the second based on the tangent stiffness of the structure. In addition, the stiffness-based vulnerability theory was seen to be used to identify the collapse mechanism or failure scenarios Ye, Liu, & Pan, 2011).…”
Section: Deterministic Indicesmentioning
confidence: 99%
“…The stiffness-based judgment method determines the importance of a single element by studying its contribution to the overall structural stiffness (e.g., tangential stiffness). The tangential stiffness matrix contains structurally specific information, and its singularity can reflect structural safety [10]. However, the topology judgment that purely depends on the structural stiffness is divorced from the load effect, and the complex algorithm involved has a high threshold in engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the determinant of the stiffness matrix of the structure is closely related to the safety of the structure, and the importance coefficient of the element can be defined from the material stiffness matrix of the structure [23]. Based on previous research about the robustness, new theories or methods to element importance have been proposed successfully using new judgment indicators, where most are for frame structures, and a few are for grid structures [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%